QASHASH: CREATING SMART PEOPLE - Abu Yazid Bustami Harahap; M. Iqbal Irham (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This article describes the qashash or stories contained in the Qur'an which are used as a method to create intelligent and monotheistic people. The stories of the Qur'an are useful in the formation of human characters who are virtuous and have the creed of monotheism. The stories of the Qur'an become part of an effective educational method for the formation of a soul that unites God. So that it will produce intelligent humans. With stories or stories, students will get a touch of values that will affect their character. An educator can use stories as an alternative method of forming students' souls, especially in the affective and psychomotor domains. The research method in writing this article is a qualitative approach, tahlili interpretation.